PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SAUS DUA BELIBIS PADA PT ANGGANA CATUR PRIMA DI JAKARTA - Sumardi, Sumardi; siswanto, Anis Illahi (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2022)
The goal of this scientific article is to determine and assess the impact of brand image and promotion on Dua Belibis sauce buying decisions. The design of the research is associative research, then the data obtained for both primary and secondary data are obtained from various literature studies. In addition, data were also collected and scored using a Likert Scale measurement. The brand image and the promotion as a control variables has a favorable and significant impact on purchase decisions. The most important factor influencing consumers' purchasing decisions when it comes to Delmonte sauce is promotion. The adjusted R Square value is 0.281, indicating that 28.1 percent value of the dependent variable can also be explained by the independent factors, namely brand image and promotion, while the remaining 71.9 percent cannot be explained yet by variables that addressed in this study. Keywords: promotion, brand image, purchase decision, branding